Current practices for assessing usability of novel point-of-care diagnostics for infectious diseases: a scoping review protocol - Castro, María del Mar; Ismail, Horeya M.; Montenegro-Quiñonez, Carlos Alberto; Reipold, Elena Ivanova; Shilton, Sonjelle; Denkinger, Claudia M.; Yerlikaya, Seda (BMJ open, 2025)
Introduction Novel diagnostics, particularly point-of-care (POC) tests, play a crucial role in the early detection and management of infectious diseases, especially in resource-limited settings. Ensuring test performance and quality while minimising the risk of human error becomes more relevant when shifting testing tasks from highly controlled settings like centralised laboratories to people with minimal training. Applying usability and human factors engineering principles can reduce the challenges related to human errors. Despite existing frameworks and tools, the practical application of usability guidelines remains variable across different settings. - Methods and analysis This scoping review protocol outlines a systematic investigation of current practices in assessing the usability of novel diagnostics, particularly POC tests for infectious diseases intended for use in low-income and middle-income countries. The review will analyse original research studies of all designs and product dossiers that report on the usability evaluation or validation of a diagnostic test for an infectious disease. A qualitative synthesis of the data extracted from the articles will be conducted. We will follow the Preferred Reporting Items for Systematic Reviews and Meta-Analyses Protocols and the Joanna Briggs Institute guidelines for this scoping review. - Ethics and dissemination No ethical approval is required because individual patient data will not be included. The findings will be disseminated through publication in a peer-reviewed journal.
Gesehen am 12.12.2025